Root exudates in controlled environment agriculture: composition, function, and future directions - Camli-Saunders, Deniz; Villouta, Camilo (Frontiers in Plant Science, 2025)
Two decades of research has revealed an intricate network of root exudates in plants, which they use to interact with and mediate their surrounding environment, the rhizosphere. Prior research has been conducted mainly on model plants such as Arabidopsis or staple monoculture crops like maize, soybean, and rice, revealing crucial roles in plant growth, microbiota interaction, nutrient acquisition, and bioremediation. However, similar research has only begun to be conducted in Controlled Environment Agriculture (CEA) systems, leaving a considerable knowledge gap in the mechanisms, impacts, and uses of exudates in CEA. Exhaustive literature searches revealed less than two dozen articles with direct implications in CEA vegetable crop exudates. This review synthesizes the existing literature to examine the composition, functions, and influences of vegetable root exudates within CEA systems. The first section explores key compounds —including amino and organic acids, and sugars— along with mechanistic processes, and microbial interactions. The second section compares root exudates in soil-based versus hydroponic CEA systems based upon differences in substrate, (a)biotic stressors, microorganisms, and nutrient availability. By contrasting existing literature on both CEA soil-based and hydroponic systems, the section examines likely differences in exudate composition, mechanisms, and functions. The final section presents case studies from both hydroponic and soil based systems, highlighting how root exudates contribute to environmental stress mitigation, allelopathy, disease response, bio/phytoremediation, and pest control. It reveals major avenues for the use of exudates in CEA systems worldwide. Lastly, we ponder the future avenues of exploration for CEA root exudates, proposing the creation of a database for usage in smaller or organic farms and in urban agriculture settings. In conjunction, we emphasize the need for further investigation into the potential of exogenous applications of exudate-like compounds to positively impact yield, disease resistance, soil restoration, and land reclamation, especially in the context of climate change.